Using inventions in the public domain a guide for inventors and entrepreneurs - World Intellectual Property Organization (Geneva, Switzerland WIPO, 2020)
This guide is designed to help researchers, inventors and entrepreneurs gain access to and use technology and business information and knowledge in the public domain, for the development of new innovative products and services in their own country. The focus of the guide is on information and technology disclosed in patent documents. Designed for self-study, the guide provides easy-to follow training modules that include teaching examples and other useful practical tools and resources. Esta guía está diseñada para ayudar a los investigadores, inventores y empresarios a acceder y utilizar la tecnología y la información comercial y el conocimiento en el dominio público, para el desarrollo de nuevos productos y servicios innovadores en su propio país. La guía se centra en la información y la tecnología divulgadas en los documentos de patente. Diseñada para el autoaprendizaje, la guía proporciona módulos de capacitación fáciles de seguir que incluyen ejemplos de enseñanza y otras herramientas y recursos prácticos útiles.
Keywords: PATENTES -- INVENTOS -- PROPIEDAD INTELECTUAL -- DERECHOS DE AUTOR -- INVENTOS E INVENTORES